5.4k views
1 vote
What is the answer i’m dumb ‍♀️‍♀️

What is the answer i’m dumb ‍♀️‍♀️-example-1
User Rekire
by
5.3k points

2 Answers

2 votes

Answer:

C. 4g^2+9g-3

Explanation:

(7g^2+5g-1)-(3g^2-4g+2)

subtract each term individually

(7g^2-(3g^2))=(4g^2)

(5g-(-4g))=(5g+4g)=(9g)

((-1)-(2))=(-3)

((7g^2-(3g^2))+(5g-(-4g))+((-1)-2))

4g^2+9g-3

User Sahar Millis
by
5.7k points
3 votes

Ah, subtracting polynomials.

The answer requires you to find the difference of
7g^(2)  + 5g - 1 and
3g^(2)  - 4g + 2.


7g^2 + 5g - 1\\ - 3g^2 - 4g + 2


7g^2 - 3g^2 = 4g^2


5g - (-4g) = 5g + 4g = 9g


-1 - 2 = -3

Then, just put everything together.


4g^2 + 9g - 3

So, the answer would be choice c.

User Tdemay
by
5.7k points